2012
DOI: 10.1103/physreve.85.011149
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and age structure in spatial games

Abstract: We study the evolution of cooperation in evolutionary spatial games when the payoff correlates with the increasing age of players (the level of correlation is set through a single parameter, α). The demographic heterogeneous age distribution, directly affecting the outcome of the game, is thus shown to be responsible for enhancing the cooperative behavior in the population. In particular, moderate values of α allow cooperators not only to survive but to outcompete defectors, even when the temptation to defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 59 publications
0
48
0
2
Order By: Relevance
“…Other approaches facilitating the evolution of cooperation include the introduction of noises to payoffs and updating rules [22][23][24][25][26][27], asymmetry between interaction and replacement graphs [28,29], diversity [30][31][32][33][34], differences between time scales of game dynamics [33,[35][36][37], interaction stochasticity [38], as well as the adoption of simultaneous different strategies against different opponents [39]. Somewhat more personally-inspired features supporting the evolution of cooperation involve memory effects [40], heterogeneous teaching activity [41][42][43], preferential learning [44,45], aspiration [46][47][48], age [49], rationality [50], myopically selective interactions [51,52], local contribution [53], and coevolutionary partner choice [54][55][56][57], to name but a few examples studied in recent Email address: yongkuiliu@163.com (Yongkui Liu).…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches facilitating the evolution of cooperation include the introduction of noises to payoffs and updating rules [22][23][24][25][26][27], asymmetry between interaction and replacement graphs [28,29], diversity [30][31][32][33][34], differences between time scales of game dynamics [33,[35][36][37], interaction stochasticity [38], as well as the adoption of simultaneous different strategies against different opponents [39]. Somewhat more personally-inspired features supporting the evolution of cooperation involve memory effects [40], heterogeneous teaching activity [41][42][43], preferential learning [44,45], aspiration [46][47][48], age [49], rationality [50], myopically selective interactions [51,52], local contribution [53], and coevolutionary partner choice [54][55][56][57], to name but a few examples studied in recent Email address: yongkuiliu@163.com (Yongkui Liu).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17]. In particular, network reciprocity [11,[18][19][20], whose principle has an appealing physical interpretation (cooperators are better off when they are surrounded by cooperators), has recently attracted interest in the physics community [21][22][23][24][25][26][27][28][29][30][31][32][33]. Quite interestingly, it has been found that, in contrast to what happens in spatially homogeneous (wellmixed) populations, the arrangement of individuals according to certain topologies can lead to very different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…After the seminal paper, a large amount of works are devoted to exploring factors of promoting cooperation on lattices, such as, punishment and reward [8][9][10], reputation [11,12], weight [13,14], age structure [23], and others (see [16][17][18][19][20][21][22]), etc.…”
Section: Introductionmentioning
confidence: 99%